Anatomical and histological assessment of left bundle branch area pacing in human heart with refractory heart failure. (17th January 2022) - Zhang, Jiefang; Pan, Yiwen; Sun, Yaxun; Fu, Guosheng
Abstract: As an emerging pacing technique, left bundle branch area pacing (LBBAP) has served as a physiological pacing modality that overcomes the limitations of His bundle pacing (HBP) or right ventricular pacing. Three patients with terminal heart failure who were waiting for heart transplantation and met the indications of pacemaker implantations received LBBAP. Symptoms were relieved and stabilized and eventually received heart transplantation. Diseased hearts from the recipients were dissected post‐transplantation, and the direct visual of pacing lead locations in the interventricular septum were evaluated, and the histopathological examination around the lead was conducted for the first time in human. As a result, we found that the locations of LBBAP leads were matched with fluoroscopic views during the procedure and Masson's staining showed extensive fibrosis occur around the lead but did not result in high thresholds.